Translation and validation of the Transition Readiness Assessment Questionnaire (TRAQ) - Catherine G. Anelli; Claudio A. Len; Maria Teresa R.A. Terreri; Gleice C.S. Russo; Andreas O. Reiff (Brazilian Society of Pediatrics, 2019)
Objective: To translate and validate the Brazilian Portuguese version of the Transition Readiness Assessment Questionnaire in a population of adolescents and young adults with chronic rheumatologic disorders. This questionnaire evaluates the patient's readiness for making the transition from the pediatric health service to adult care. Methods: The four‐phase methodology for the translation and validation of generic questionnaires was followed, including translation, back‐translation, pilot testing and clinical validation of the final tool. The confirmatory factor analysis was used for clinical validation and the Cronbach's alpha coefficient was used to assess the overall internal consistency of the final tool. Results: A total of 150 patients with a mean age of 17.0 years (SD = 2.2 years, range 14-21 years) were enrolled for the final tool validation. Of those, 71 patients had juvenile systemic lupus erythematosus (47.3%), 64 had juvenile idiopathic arthritis (42.7%), and 15 had juvenile dermatomyositis (10%). During the confirmatory factor analysis, the dimension "Talking with providers" consisting of two questions, was considered as not fitting the translated questionnaire due to a very high ceiling effect and was therefore excluded. All other translated items favorably contributed to the overall consistency of the final tool; removing that dimension did not result in a substantial increase in Cronbach's alpha, which was 0.776. Conclusions: The Brazilian Portuguese version of the Transition Readiness Assessment Questionnaire was validated in a population of transitional patients with chronic rheumatologic disorders, after one dimension from the original questionnaire was excluded. It is a non‐specific disease questionnaire; thus, it can be used to evaluate the transition readiness of Brazilian patients with other chronic diseases. Resumo: Objetivo: Traduzir para o português brasileiro e validar o Questionário de Avaliação do Preparo para a Transição em uma população de adolescentes e adultos jovens com doenças reumáticas crônicas. Este questionário avalia o preparo do paciente para realizar a transição do serviço de saúde pediátrico para a assistência ao adulto. Métodos: Seguimos a metodologia de quatro etapas para a tradução e validação de questionários genéricos que inclui tradução, retrotradução, teste piloto e validação clínica do instrumento final. Utilizamos Análise Fatorial Confirmatória e Coeficiente Alfa de Cronbach para testar a validade do instrumento e sua consistência interna. Resultados: Responderam ao questionário traduzido e adaptado 150 pacientes. A média de idade foi de 17,0 anos (DP = 2,2 anos, variação 14‐21 anos). Tinham o diagnóstico de lúpus eritematoso sistêmico juvenil 71 pacientes (47,3%), 64 (42,7%) artrite idiopática juvenil e 15 (10%) dermatomiosite juvenil. Durante a análise fatorial confirmatória, a dimensão "Falando com a Equipe Médica" contendo duas questões teve que ser removida devido à presença de expressivo efeito teto. Todas as outras questões restantes contribuíram favoravelmente para aumentar a consistência interna do questionário, obteve‐se um Coeficiente Alfa de Cronbach de 0,776. Conclusões: O Questionário de Avaliação do Preparo para a Transição na sua versão em português brasileiro pode ser validado em uma população de pacientes com doenças reumáticas crônicas em transição, com a exclusão de uma dimensão do questionário original. Por ser um questionário não específico para doenças reumáticas, poderá ser utilizado para avaliar o preparo para a transição de outros pacientes brasileiros com doenças crônicas. Keywords: Transition readiness tool, TRAQ, Brazil, Rheumatology, Adolescent health services, Research in health services, Palavras‐chave: Avaliação do preparo para a transição, TRAQ, Brasil, Reumatologia, Serviços de saúde do adolescente, Pesquisa em serviços de saúde